Encyclopedia of lesbian, gay, bisexual, and transgender history in America - Stein, Marc (Charles Scribner's Sons/Thomson/Gale, 2004)
A three-volume survey of more than 400 years of lesbian and gay history and culture in the United States, presented through over 500 alphabetically arranged entries. Coverage includes people, public policy, economics, social issues, identities, and culture, among many others. For students, researchers, and general readers.
Keywords: amériques; encyclopédie; identités LGBTQIA2+; outils; ouvrages de références; ressource en ligne; régions géographiques; états-unis